Papua Separatis Terrorist Groups Detection Through Osint and Counter Intelligence Effort (Osint Detection Study On The Baintelkam Polri Separatist Management Unit) - Maekel Eugaliel Pindonta Sembiring; Arthur Josias Simon (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The Separatist Terrorist Group Movement (KST) is a group that demands independence or secession from Indonesia. Public demand for the police as a public institution that maintains the national security of the Republic of Indonesia is a big responsibility that must be implemented. The Separatist Terrorism Group (KST) movement and researchers will also analyze the role of the National Police's Baintelkam Separatist Countermeasures Unit in collecting OSINT-based information which is then processed into intelligence information, especially in terms of identifying threats that could threaten state sovereignty. The type of research used is qualitative research, the data collection strategy chosen is a qualitative data collection strategy. The results show that the large-scale use of OSINT has created new contexts and perspectives that help intelligence and security services to better understand the complexities of certain security developments in local or national contexts. On the movement of KST, among others. The intelligence community analyzes and collects data from all available open sources to try to find interesting data in the large amount of free information available.